Polymeric nanofibers as advanced probiotic carriers: Production strategies, functional performance, and emerging applications - de Oliveira Filho, Josemar Gonçalves; Egea, Mariana Buranelo; Zhang, Wanli; Pandi, Ananthi; Sivieri, Katia [UNESP]; Salgaço, Mateus Kawata [UNESP]; Sentanin, Leonardo; Braga, Anna Rafaela Cavalcante; da Silva, Michael Jones [UNESP]; Mattoso, Luiz Henrique Cappareli (Elsevier, 2025)
In recent years, the incorporation of probiotics into polymeric nanofibers has emerged as a promising strategy for protecting and enabling the controlled release of these beneficial microorganisms, enhancing their stability and functional effectiveness. This review aims to provide a comprehensive overview of the incorporation of probiotics into nanofibers, emphasizing the advantages of nanofiber-based systems for encapsulation and controlled release. Our text explores the techniques for nanofiber production, the challenges in maintaining probiotic viability, and their potential applications in the food, pharmaceutical, and agricultural industries. Incorporating probiotics into nanofibers holds promising applications by enabling protection and controlled release. However, most studies remain in vitro, highlighting the need for in vivo validation. Conventional production methods, like electrospinning, face scalability challenges, making alternative techniques such as Solution Blown Spinning a viable option for industrial application. Additives such as stabilizing and bioactive compounds have been added to fiber-forming dispersions to stabilize bacteria and thus improve their survival during electrospinning and storage. Future research should optimize these approaches to enhance probiotic stability and functionality in final products.